Perkembangan Konsep Budgeting dalam Era Transformasi Digital - Sinbi Fitria Utami; Sofia Maryam Fauziah; Maya Rosmayanti; Haifa Aulia Nurshafiyyah Subagja; Suhendi Suhendi (Sekolah Menengah Kejuruan (SMK) Pustek, 2026)
The rapid advancement of digital technology has challenged the relevance of traditional budgeting, which tends to be rigid and less adaptive to dynamic business environments. Despite increasing adoption of digital systems, there remains limited integrative understanding of how budgeting concepts evolve and how such transformation influences decision-making quality. This study aims to examine the shift from traditional to digital budgeting, identify key driving factors, and analyze its implications for organizational decision-making. The research employs a qualitative approach using a structured literature review of recent academic publications, focusing on studies related to financial management and digital transformation. The findings show that digital budgeting enables real-time data integration, improves transparency, and enhances efficiency in financial planning processes. Furthermore, it contributes to more timely and data-driven decision-making. However, the study also identifies several challenges, including data security risks, system integration complexity, and gaps in digital competencies. Overall, the evolution of budgeting reflects a transition toward a more adaptive and strategic approach, where effectiveness depends not only on technological capability but also on organizational readiness and managerial judgment.